Development of technological processes of vibration machine long container from composite materials - Романченко, Алексей Владимирович (Technology audit and production reserves, 2015)
Relevance of the use of new materials for creation of vibrating machine U-shaped container established. Researches by selection of long container vibration machine design scheme made of composite materials presented in the article. Experimental researches by choice of container composite material are shown. Composite materials based on cold curing epoxy compositions and polyester resin hot curing chosen for researches. The results of composite samples tests analyzed. Based on the test results of fiberglass samples plotted breaking stress and changes in strength for epoxy and polyester fiberglass models, depending on fiber tissue percentage. Optimal materials for the creation of U-shaped long container selected. The technological process of manufacturing the vibration machine container intended for long type details treatment. Detailed description of the preparatory and basic operations of container manufacturing are shown in the article.